Apples Pulp (Pyrus malus) Nutritional Profiling Evaluation of Various Varieties of Balochistan - Aziz, Mohammad; Jadoon, Saima; Sh., Ziviqar (Pakistan Journal of Nutrition, 2013)
The object of this study was to evaluate the nutritive composition of different verities of apples for this twenty different verities of apples commonly available in Balochistan namely Amri, Bluish golden, Bonza, Discovery, Elastar, Florina, Gala, Gloster 69, Golden delicious Grany Smith, Green Sleeves, Ida Red, Kidds orange, Mushadi, Red delicious, Summer red, Tydes Menearly, Samootree, Kaja and Spartan have been quantitatively analyzed using Atomic Absorption Spectroscopy, Flame Photometry and other chemical methods. Results show that the fat soluble vitamin A is 0.89mg/100gm (mean) on the other hand the concentration of water soluble vitamin C is 3.8mg/100gm, The mean composition of different mineral is as follows sodium 10.06mg/100gm, potassium 84.43mg/100gm, calcium 15.67mg/100gm, magnesium 11.08mg/100gm, Iron 5.78mg/100gm and phosphorus 12.19mg/100gm. Average Weight and volume of amri apple were comparatively higher i.e., 104.6 gm and 129mL as compared with others. The median pH value is 3.91, the median percentage of moisture, ash and brix is 81.95%, 1.63% and 15.02%, respectively. The percentage of Fat lies between 0.2-5.15%, Fiber lies b/w 1.13 -8.60%, protein lies b/w 0.17-0.74% and pectin lies b/w 0.43-1.63%. The highest value of total sugar of Samootree is comparatively high i.e., 20.13, the concentration of reducing sugar in kaja were comparatively low i.e., 7.10 and the concentration of non reducing sugar in Green Sleevesis was comparatively higher than other verities i.e., 7.92.